Manajemen Mutu Terpadu pAda Institusi Pendidikan - Inan Tihul (STIT Muslim Asia Afrika, 2019)
The main problems of education is an increasing of quality for kinds, levels, and educational segments. There for in this case the gover-ment launch the eight quality national standards. Processing quality of education must have been supported by personnel such as administrator, teachers staff, counselor, and a national quality of administrator staff. That matter is also supported by the edu-cational structures, and infrasrtuctures, facilities, media, quantity, and qua-lity learning sources appropriate, and the proportional financial, established management, also supported enviroment. The quality focuses on happiness and happily of customers and more than just customers satisfying.used approaching to explain about the charac-teristic of MMT is inputting, processing, and outputting.